Intraoperative Complications and Mid-Term Follow-Up of Large-Diameter Head Metal-on-Metal Total Hip Arthroplasty and Hip Resurfacing Arthroplasty. (June 2018) - Miettinen, S. S. A.; Mäkinen, T. J.; Mäkelä, K.; Huhtala, H.; Kettunen, J. S.; Remes, V.
Background and Aims: Large-diameter head total hip arthroplasty and hip resurfacing arthroplasty were popular in Finland from 2000 to 2012 for the treatment of hip osteoarthritis. The aim of this retrospective study was to investigate the mid-term survival of large-diameter head total hip arthroplasty patients operated on in three university hospitals and to compare these results to the survival of hip resurfacing arthroplasty patients. Material and Methods: A total of 3860 hip arthroplasties (3029 large-diameter head total hip arthroplasties in 2734 patients and 831 hip resurfacing arthroplasties in 757 patients) were operated on between January 2004 and December 2009. The mean follow-up was 4.3 years (range: 0.3–8.0 years) in the total hip arthroplasty group and 5.1 years (range: 1.7–7.9 years) in the hip resurfacing arthroplasty group. Cox multiple regression model and Kaplan–Meier survival analysis were used to study the survival of the total hip arthroplasties and the hip resurfacing arthroplasties. Intraoperative complications and reasons for revisions were also evaluated. Results: In Cox regression analysis, the hazard ratio for revision of hip resurfacing arthroplasty was 1.5 compared with large-diameter head total hip arthroplasty (95% confidence interval: 1.0–2.2) ( p = 0.029). The cumulative Kaplan–Meier survival rate was 90.7% at 7.7 years for the large-diameter head total hip arthroplasty (95% confidence interval: 86.8–94.6) and 92.2% at 7.6 years for hip resurfacing arthroplasty (95% confidence interval: 89.9–94.6). There were a total of 166/3029 (5.5%) intraoperative complications in the large-diameter head total hip arthroplasty group and 20/831 (2.4%) in the hip resurfacing arthroplasty group ( p = 0.001). Revision for any reason was performed on 137/3029 (4.5%) of the arthroplasties in the large-diameter head total hip arthroplasty group and 52/831 (6.3%) in the hip resurfacing arthroplasty group ( p = 0.04). Conclusion: The mid-term survival of both of these devices was poor, and revisions due to adverse reactions to metal debris will most likely rise at longer follow-up. There were more intraoperative complications in the large-diameter head total hip arthroplasty group than in the hip resurfacing arthroplasty group.